Modeling of the Forming Process for Aluminum Detail - Lyashenko, V.; Matarneh, Rami; Sotnik, S.; Belova, N. (Scholars Middle East Publishers, 2018)
In the work, modeling of the forming process for aluminum detail was carried out. As a detail, "Pen" is chosen for which the material AK6M2 is determined, taking into account its physico-chemical properties. In the beginning, a 3D detail model is constructed, using the SolidWorks program. Then in the program Nova Flow, entire process of filling the mold in real time, rate of filling the mold cavity with metal, hardening time of the casting was determined. The temperature change dynamics of the casting after filling the mold is investigated. Possible nodes are susceptible to formation of shrinkage shells.
Keywords: modeling; casting; aluminum; part